VIBRATION SENSOR BASED ON FLAT KOIL FOR EARTHQUAKE EARLY DETECTION IN LOMBOK NUSA TENGGARA BARAT REGION - Islahudin Islahudin; M. Firman Ramdhan (IKIP Mataram, 2013)
In this research has been developed the application of flat coil as vibration sensor for early detection of earthquake. The flat coil is a very thin wire winding and acts as an inductor. This flat coil along with the capacitor constructs an oscillator which generates frequencies depending on the value of inductance and capacitance. This oscillator is called the LC oscillator. The flat coil inductance depends on the distance of the metal object in front of the flat coil. If the inductance changes, the frequency will change as well. Frequency can be converted into voltage form to represent distance. This effect is then applied to low frequencies using a pendulum on the sensor housing. The sensor system created can measure low-frequency vibrations in the range 0.26 - 1.0 Hz. Based on the research, the vibration sensor that has been made can measure one of the low frequency vibrations of 0.468 Hz at the frequency of 0.46 Hz vibration source